TRANSFORMASI INDUSTRI 4.0 SEBAGAI VARIABEL MEDIATOR: ANALISIS DAMPAK KOMISARIS INDEPENDEN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA PERUSAHAAN - ADIMAN, RAJA MULTI KONVOKESEN; SILKFAN, RARA; NURFITRIANI, NURFITRIANI; HAMID, M; AZWIR, MAHARANI (JURNAL AKUNTANSI DAN KEUANGAN, 2025)
This research examines the mediating effect of Industry 4.0 adoption on the relationship between independent commissioners, institutional ownership, and corporate performance, as measured by Earnings per Share (EPS), in manufacturing firms listed on the Indonesia Stock Exchange from 2016 to 2023. In the context of rapid digital transformation, companies are increasingly required to integrate sophisticated technologies, including automation and data analytics, into their operations. Independent commissioners are expected to enhance oversight and ensure that technological initiatives comply with regulatory and ethical frameworks, while institutional investors can reinforce managerial discipline and support long-term innovation. The study incorporates firm size (logarithm of assets) and leverage ratios (DAR and DER) as control variables to assess their impact comprehensively. Employing multiple regression analysis, the findings provide empirical evidence that both independent commissioners and institutional shareholders influence corporate performance not only directly but also indirectly through digital transformation. The results highlight the strategic importance of governance structures and technology adoption for achieving sustainable financial performance in the Industry 4.0 era.